The Influence of Institutional Environment, Experience, and Education on Social Entrepreneurship - Rodhiah Rodhiah; Nur Hidayah (International Journal of Management Science and Application, 2023)
Social entrepreneurship is an economic field that aims to provide social benefits to the surrounding community, especially in terms of improving welfare through innovation and the application of entrepreneurial concepts so that it has economic value, therefore social entrepreneurship plays an important role in advancing the country's economy. In social entrepreneurship, several approaches are applied, namely practical, innovative, and sustainable approaches that can certainly have a positive impact on the lower economic class or underprivileged communities. As is known, every aspect, including social entrepreneurship, must have factors that affect its sustainability, both factors that encourage an increase in social entrepreneurship intentions support the creation of social entrepreneurship or inhibit factors that hurt social entrepreneurship. For this reason, this quantitative research aims to find out things that affect social entrepreneurship, especially whether, the institutional environment and education have a positive influence on entrepreneurship. This research was conducted on students at Tarumanagara University, sampling was carried out using purposive sampling techniques so that the samples taken could be by the purpose of the study, namely provided that respondents had passed entrepreneurship courses which later data collection would be carried out through questionnaires, then the data would be processed using the help of smart PLS. The results showed that there was a positive and significant influence between the institutional environment and social entrepreneurship. There is a positive influence between education and social entrepreneurship.